Subjective Well-Being Factors in Students - Doriza, Shinta; Fasah Ilwana, Hilwa; Nugraheni, Prastiti Laras (Journal of Family Sciences, 2024)
Subjective well-being in college students is formed by various factors that can impact their mental and emotional state. This study aims to see the dominant factors that shape the subjective well-being of college students. The method used in this study is a quantitative method with a confirmatory factor analysis approach. This study involved 349 students from private universities in the East Jakarta area—data collection using questionnaires distributed through social media. The results showed that the order of the largest factor loading was the psychological well-being factor, the relationships factor, and the physical health and well-being factor, with a Keiser-Meyer-Olkin (KMO) value of 0.758. This research implies that universities can focus more on improving physical health and well-being to not hinder student activities in lectures, such as maintaining sleep quality and other daily activities.